(untitled) (Proceedings of International Educators Conference, 2024)
Studying the biology of flowering and pollination of rare plants is a major challenge in assessing their self-preservation and population stability. Dorema microcarpum Korov is a plant species included in the Red Book of the Republic of Uzbekistan and has not been studied before. The purpose of our research is to study the features of anechological and phenological phases of D. microcarpum Korov in Pop hills of Namangan region in 2020-2023, to determine the rules of flowering, canopy and general synflorescence under natural conditions.